Dakwah Digital menggunakan Media Instagram (Kajian Ekonomi Islam pada Akun @ruanghalal) - Hidayatullah, Muhammad Syarif (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2020)
The implication of our entry into the era of disruption is a wave of digitalization that makes a shift of routine from the real world to the virtual world. The positive thing that can be done is the use of technology to help in da’wah. Internet-based da'wah through social media is a dynamic response to the era of disruption and social media that is so popular with the millennial generation is Instagram. The @ruanghalal Instagram account is one of the da'wah subjects present and the da'wah material presented focuses on Islamic economic studies. Digital da'wah with Islamic economic studies on the @ruanghalal account is carried out by presenting descriptive content through explanatory text supported by visual illustrative images and utilizing features provided by Instagram. The discussions that are displayed are not stagnant or out of date, but are diverse and respond to current developments and financial transactions.